Accuracy assessment of Smart stereolithography models generated by Dental Monitoring®: A pilot study - Vassis, Stratos; Karamalaki, Dimitra; Liu, Jason; Noeldeke, Beatrice; Sefidroodi, Mohammedreza; Srivastav, Sukeshana; Woolley, Julian; Stoustrup, Peter (Korean journal of orthodontics (2012), 2025)
This pilot study aims to evaluate the clinical accuracy of Smart stereolithography (STL) files generated by the Dental Monitoring® (DM) system by comparing them with gold standard intraoral scans (IOSs). Seven aligner patients using the DM application were included. For each patient, Smart STL files generated from remote scans were superimposed onto IOSs using the best-fit algorithm in OnyxCeph software. Differences regarding inclination, angulation, rotation, buccal/lingual, mesial/distal, and intrusion/extrusion were quantified and statistically compared. Statistically significant differences were observed in inclination, mesial/distal, and buccal/lingual movements, particularly in the posterior segments. However, all deviations remained within clinically acceptable thresholds for single aligner tooth movement. Despite minor deviations, Smart STL files generated by DM demonstrated sufficient accuracy for use in aligner planning and refinement. These findings highlight the potential of DM-generated Smart STL files for subsequent aligner treatment.